UPAYA MENUMBUHKAN SEMANGAT KEISLAMAN MELALUI MAJELIS ILMU DI MASJID JANWAR AL-HIDAYAH - Hamzah Irfanda; Khairani, Lily; Zahara, Aulia; Purnama Sari, Leni; Rahmaneli, Nadya (Jurnal Peduli : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to describe the efforts to foster Islamic enthusiasm through the activities of religious gatherings (majelis ilmu) at Janwar Al-Hidayah Mosque. As a center of worship and Islamic education, the mosque plays a strategic role in shaping the religious character of the community. Majelis ilmu serves as an effective medium to strengthen religious understanding, enhance Islamic brotherhood, and raise spiritual awareness among the congregation. The research employs a qualitative descriptive method with a field study approach through observation, interviews, and documentation. The findings indicate that regular religious gatherings significantly increase the congregation’s religious knowledge, motivate the youth to be actively engaged in Islamic activities, and reinforce faith and piety values. Therefore, the majelis ilmu at Janwar Al-Hidayah Mosque plays an essential role in nurturing a knowledgeable, ethical, and committed Muslim generation